2016
DOI: 10.1007/s12298-016-0347-1
|View full text |Cite
|
Sign up to set email alerts
|

Determining the most effective traits to improve saffron (Crocus sativus L.) yield

Abstract: To determine the effective traits to improve saffron yield, a split plot design based on RBCD was done in Mashhad region in Iran for three years (2012-2014). The results showed that all traits except number of daughter corm, fresh weight of daughter corm and dry leaf weight had low general heritability. Results of genotypic and phenotypic coefficients of variation and genetic advance demonstrated that the majority of traits had a low diversity and the selection did not have any effect in improving the traits. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 31 publications
0
9
0
1
Order By: Relevance
“…Each corm can produce one to four apical shoots containing developing flower and leaf (Ali et al, 2018). Mother corm size and weight have a significant impact on flowering and the number of daughter corms produced (Ali et al, 2018;Bayat et al, 2016;Douglas et al, 2014). Small mother corms (<1 cm diameter and <6 g fresh weight) do not flower and produce nonflowering cormlets (Ali et al, 2018;Douglas et al, 2014).…”
Section: Effects Of Growing Substrates and The Mode Of Nutrient Supplymentioning
confidence: 99%
“…Each corm can produce one to four apical shoots containing developing flower and leaf (Ali et al, 2018). Mother corm size and weight have a significant impact on flowering and the number of daughter corms produced (Ali et al, 2018;Bayat et al, 2016;Douglas et al, 2014). Small mother corms (<1 cm diameter and <6 g fresh weight) do not flower and produce nonflowering cormlets (Ali et al, 2018;Douglas et al, 2014).…”
Section: Effects Of Growing Substrates and The Mode Of Nutrient Supplymentioning
confidence: 99%
“…Some studies have demonstrated that the optimum period for planting saffron corms is between June 5 and July 5, i.e., immediately after corms enter dormancy (Bayat et al 2016). These periods are suitable for Note: F statistics and P values of two-way ANOVAs are presented for autumn and spring emergence, testing the effect of planting date, year of planting and their interaction.…”
Section: Planting Periodmentioning
confidence: 99%
“…The former studies indicated that path analysis is more efficient than correlation coefficients determining the relationships among the features (BAHRAMINEJAD et al, 2011;DARVISHZADEH et al, 2011). Correlation coefficient and path analysis have been employed by many researchers (TALEBI et al, 2007;BEHRADFAR et al, 2009;BAYAT et al, 2016;JOCKOVIĆ et al, 2015) to distinguish relevance among the quantitative characters.…”
Section: Introductionmentioning
confidence: 99%